Identification of Factors Influencing Anemia among Children Aged 6–59 Months in Ethiopia Using Ethiopia Demographic and Health Survey 2016 Data - Woldegebriel AG; Gebrehiwot GG; Desta AA; Ajemu KF; Berhe AA; Woldearegay TW; Bezabih NM (Dove Medical Press, 2021)
Ataklti Gebretsadik Woldegebriel,1 Gebremedhin Gebreegziabiher Gebrehiwot,2 Abraham Aregay Desta,1 Kiros Fenta Ajemu,1 Asfawosen Aregay Berhe,1 Tewolde Wubayehu Woldearegay,1 Nega Mamo Bezabih1 1Department of Human Nutrition, Tigray Health Research Institute, Mekelle, Tigray, Ethiopia; 2Department of Human Nutrition, School of Public Health, Adigrat University, Adigrat, Tigray, EthiopiaCorrespondence: Ataklti Gebretsadik WoldegebrielTigray Health Research Institute, Mekelle, Tigray, 1547, EthiopiaEmail atakltigebertsadik@gmail.comBackground: Anemia is the most common nutritional problem and a widespread micronutrient-deficiency disorder on a global scale. In Ethiopia, childhood anemia is highly prevalent and a major public health concern. This study aimed to identify factors associated with anemia among children aged 6– 59 months in Ethiopia.Methods: Data weres extracted from the 2016 Ethiopia Demographic and Health Survey (EDHS). We found records for 8,603 children aged 6– 59 months in the data set. After 448 had been excluded due to incomplete records, 8,155 children were included in the final analysis. Pearson’s χ2 was used to assess associations between each factor and categorical outcome variables. Multivariate logistic regression analyses were done to determine factors associated with anemia, and significant associations were declared at p≤ 0.05 for the final model.Results: More than half (51.5%) the children were male and the overall mean age was 31.85± 15.66 months. Mean hemoglobin concentration was 10.37± 17.55 g/dL. The overall prevalence of anemia was 56.6%: 3.7%, 30.4%, and 22.5% severe, moderate, and mild anemia, respectively. Increased child age, decreased maternal age, lowest rung on wealth index, mother living alone, mother engaged in outside work, increased birth order, decreased birth interval, one antenatal care visit, severe stunting, and severe underweight were significantly associated with anemia.Conclusion: The prevalence of anemia in this study was the highest of all EDHS reports. It had increased since the preceding report (EDHS 2011), and remains the main public health concern in Ethiopia. Comprehensive intervention strategies should be put in place and tailored to different levels of government (national, regional, and district) including household- and individual-level interventions for combating childhood anemia by focusing on the identified risk factors.Keywords: anemia, associated, children, EDHS 2016, Ethiopia